A rapid flood inundation model for urban flood analyses - Obaja Triputera Wijaya; Tsun-Hua Yang; Hao-Ming Hsu; Philippe Gourbesville (MethodsX, 2023)
An efficient inundation model is required for flood early warning systems in urban areas. A 2D flood model uses a governing shallow water equation, and this model is computationally expensive despite benefiting from parallel computing techniques. As an alternative to conventional flood models, cellular automata (CA) and DEM-based models (DBMs) have been studied. CA flood models simulate floods efficiently. However, a small time step is required to ensure model stability when the grid size decreases due to its diffusive characteristics. Conversely, DBM models produce results quickly, but they only show the maximum flood extent. Additionally, pre- and postprocessing are required, which take considerable time. This study proposes a hybrid inundation model that combines the two alternative approaches, and it efficiently produces a high- resolution flood map without complex pre- and postprocessing. The hybrid model is also integrated with a 1D drainage module, and thus, the model reliably simulates urban area floods. • The rapid flood inundation model integrates CA module to simulate temporal distribution of floods and DEM module to provide details of floods. • A 1D Saint Venant equation is also solved in the rapid flood inundation model to simulate the drainage sytems in urban areas. • Two-way coupling between 2D-surface and 1D-drainag models are considered in the rapid flood inundation model.